Competitive Preferences and Ethnicity: Experimental Evidence from Bangladesh - Abu Siddique; Michael Vlassopoulos (Institute of Labor Economics (IZA), 2017)
In many countries, ethnic minorities have a persistent disadvantageous socioeconomic position. We investigate whether aversion to competing against members of the ethnically dominant group could be a contributing factor to this predicament. We conducted a lab-in-the-field experiment in rural Bangladesh recruiting males from the ethnic majority (Bengali) and an underprivileged ethnic minority group (Santal) that is severely discriminated against. We randomly assign participants into groups with different ethnic composition and elicit a measure of their competitiveness. We find that when compelled to compete, there are no ethnic differences in performance and that both ethnic groups perform better in ethnically-mixed groups than in homogeneous groups. We also find that the ethnic composition of the group of competitors is an important determinant of competitive entry and its effect varies by ethnic group. Members of the ethnic minority group are less likely to compete in groups where they are a numerical minority than when all competitors are co-ethnic, whereas the reverse is true for members of the ethnic majority group. This difference is not explained by heterogeneity in performance, risk preferences, beliefs about relative ability or various socioeconomic characteristics; instead, observed behavior seems to be driven by ethnic differences in preference for interethnic competition.
Keywords: C9; C91; C93; J15; 330; competitiveness; group composition; ethnicity; minority; identity; stereotypes; lab-in-the-field experiment